1986
DOI: 10.3928/0098-9134-19860101-11
|View full text |Cite
|
Sign up to set email alerts
|

Your Patient Is Older: What Leads to Job Satisfaction?

Abstract: What boosts the interests of nurses currently working with the aged in longterm care and acute care centers? What is necessary for nurses to take an active role in rehabilitating the aged?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…This is encouraging as it suggests that any negative personal attitudes about ageing that psychiatrists might possess are having little impact on such practice. Considerable debate has occurred in the literature about the effects of area of professional practice on attitudes towards ageing [14,15]. The present study suggests that field of psychiatric practice had no impact on attitudes towards personal ageing, although it is heartening that psychiatrists who work with the elderly tended to have more positive attitudes.…”
Section: Discussionmentioning
confidence: 54%
“…This is encouraging as it suggests that any negative personal attitudes about ageing that psychiatrists might possess are having little impact on such practice. Considerable debate has occurred in the literature about the effects of area of professional practice on attitudes towards ageing [14,15]. The present study suggests that field of psychiatric practice had no impact on attitudes towards personal ageing, although it is heartening that psychiatrists who work with the elderly tended to have more positive attitudes.…”
Section: Discussionmentioning
confidence: 54%
“…Considerable debate has occurred in the literature about the effects of area of professional practice on attitudes towards ageing [14,15]. This is encouraging as it suggests that any negative personal attitudes about ageing that psychiatrists might possess are having little impact on such practice.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that nurses who show a negative attitude toward older patients tend to emphasize custodial care while those with a positive attitude tend to emphasize a rehabilitative orientation 33 . Winger and Smyth‐Strauch reported that nurses showed a positive attitude toward older patients, but they did not want to work with them 45 . Archer points out that in order to recognize any a priori biases and effectively promote patient rehabilitation, nurses need to reflect upon their view of ageing and set values related to rehabilitation 10 .…”
Section: Elements Of Nursing In Geriatric Rehabilitationmentioning
confidence: 99%
“…In the empirical studies ( n = 23) that showed strong and moderate evidence, rehabilitation was combined with the perspectives of nurses or staff members, patients, nursing homes or rehabilitation teams 3,5 , 7,8 , 26–46 . The subjects addressed included the rehabilitation process, 3,5 nurses’ attitudes 33,44 and roles, 27 teamwork, 44 encouragement 43 and detection of disability 30 .…”
Section: Literature and Critical Appraisal Reviewmentioning
confidence: 99%
See 1 more Smart Citation